Arabic diglossia: advocating for a non-deficit model in comparative analysis of reading and language acquisition - Bergstrand Othman, Lama (Frontiers in Education, 2025)
Arabic diglossia is a linguistic scenario in which Modern Standard Arabic (MSA) and Spoken Arabic (SpA) coexist within the same community, creating a unique context for literacy development. Research on the phonological and lexical distances between these varieties reveals significant effects on performance during reading and phonological awareness (PA) tasks, which are critical components of literacy development. Researchers have indicated that the phonemic and lexical distances between MSA and SpA can complicate PA, affecting reading skills, particularly among younger students. Initially intended as a systematic review, the limited number of studies fitting the criteria of this critical review led to the adoption of a narrative review approach, allowing for a critical review of the research on the effect of phonological and lexical distance on reading processes. Although these studies show differences in performance in PA and reading tasks due to lexical distances between SpA and MSA, the author of this article suggests that diglossia should be regarded as an inherent element in its native linguistic context and thus advocates against using a deficit model to interpret the results.